2004
DOI: 10.1007/s10616-004-1099-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant protein hydrolysates support CHO-320 cells proliferation and recombinant IFN-γ production in suspension and inside microcarriers in protein-free media

Abstract: We have recently developed a protein-free medium (PFS) able to support the growth of Chinese hamster ovary (CHO) cells in suspension. Upon further supplementation with some plant protein hydrolysates, medium performances reached what could be observed in serum-containing media [Burteau et al. In Vitro Cell. Dev. Biol.-Anim. 39 (2003) 291]. Now, we describe the use of rice and wheat protein hydrolysates, as non-nutritional additives to the culture medium to support productivity and cell growth in suspension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Metabolic flux analyses showed that a peptone obtained from an animal source promoted the entry of pyruvate to TCA cycle (Bonarius et al 1996). Other studies underlined that peptones improved cell growth without increasing carbon source consumption and lactate production (Ballez et al 2004;Chun et al 2007), while ammonia production was slightly increased (Burteau et al 2003). Moreover, some authors underlined the potential use of lactate as a source of carbon after glucose depletion, triggered by plant hydrolysates (Burteau et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic flux analyses showed that a peptone obtained from an animal source promoted the entry of pyruvate to TCA cycle (Bonarius et al 1996). Other studies underlined that peptones improved cell growth without increasing carbon source consumption and lactate production (Ballez et al 2004;Chun et al 2007), while ammonia production was slightly increased (Burteau et al 2003). Moreover, some authors underlined the potential use of lactate as a source of carbon after glucose depletion, triggered by plant hydrolysates (Burteau et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these concerns and limitations, serum-free and low-serum culture media have been developed. Some of these media include natural extracts that may be of animal origin, while others have a well defined composition (Ballez et al 2004;Burteau et al 2003;Schlaeger 1996;Taylor et al 1972a;Taylor et al 1972b). Arguably, media with a well defined composition and free of any serum or natural extract are the best choice for culturing cells, specially for research purposes, but these media are expensive and their use is not widespread.…”
Section: Introductionmentioning
confidence: 99%
“…The cell line is the CHO-320 line (see [1]) and the cells are cultivated in a serum-free medium: CHO-BDM S2.2. This medium contains basal defined medium (BDM), 0.1% pluronic F68 and a solution of ITS-S (1%).…”
Section: Introductionmentioning
confidence: 99%